2005
DOI: 10.1590/s0100-06832005000300017
|View full text |Cite
|
Sign up to set email alerts
|

Espaçamento, densidade populacional e adubação nitrogenada na cultura do milho

Abstract: RESUMOA distribuição espacial de plantas por área é um recurso para aumentar a produtividade. Para materiais de alta produtividade, são necessárias mais informações quanto à resposta à adubação nitrogenada. Assim, avaliou-se na cultura do milho a influência do espaçamento, da densidade populacional e de doses de nitrogênio no teor de nitrogênio nas folhas, estimativa do teor de clorofila, número de grãos por espiga, massa de 1.000 grãos, produtividade e teor de proteína nos grãos. O trabalho foi instalado no a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 7 publications
(5 reference statements)
3
16
0
8
Order By: Relevance
“…For the densities of 60,000 and 80,000 plants ha -1 there was increase in 1000 grain weight with increasing rates of N. The density of 60,000 plants ha -1 had higher 1000 grain weight in both spacings, 0.45 and 0.90 m. This response indicates a greater effect of competition among plants in density of 80,000 plants ha -1 (Figure 2f). The variable 1000 grain weight increased linearly with N rates in both spacings, which was consistent with the results of Amaral Filho et al (2005) and Cancellier et al (2011) who found direct correlation (0.52) between the 1000 grain weight and yield, increasing yield with increasing N rates.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…For the densities of 60,000 and 80,000 plants ha -1 there was increase in 1000 grain weight with increasing rates of N. The density of 60,000 plants ha -1 had higher 1000 grain weight in both spacings, 0.45 and 0.90 m. This response indicates a greater effect of competition among plants in density of 80,000 plants ha -1 (Figure 2f). The variable 1000 grain weight increased linearly with N rates in both spacings, which was consistent with the results of Amaral Filho et al (2005) and Cancellier et al (2011) who found direct correlation (0.52) between the 1000 grain weight and yield, increasing yield with increasing N rates.…”
Section: Resultssupporting
confidence: 90%
“…At the rates 80 and 120 kg N ha -1 , the density of 60,000 plants showed larger number of grains per ear than 80,000 plants (Figure 2e). However, both densities showed a linear increase for number of grains per ear with increasing N rates, which was also reported by Amaral Filho et al (2005). Significant interaction was found for this variable between plant density and spacing, since the population of 60,000 plants ha -1 showed a similar number of grains per ear in both spacings of 0.45 and 0.90 m, while the population of 80,000 plants ha -1 had higher means in the spacing 0.45 m (Table 2).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…IAC TC-01 under a row spacing of 0.60 m presented lower grain weight than at 0.40 and 0.80 m. In contrast, IAC 12 and Zelia were not affected by row spacing. To date, no impact of row spacing on grain weight has been reported (Flesh & Vieira, 2004;Amaral Filho et al, 2005;Demétrio et al, 2008).…”
Section: Resultsmentioning
confidence: 99%